Camarillo and Oxnard Airport Authorities Minutes for August 12, 1999, Amendments to Oxnard Airport Master Plan, Restrictions Upon Hours of Operation of the Oxnard Airport Terminal Building, and Oxnard Flight Schedule - Rodney L. Murphy::::::; John K. Flynn:::::: (1999)
The agenda for a meeting on December 9, 1999 between the Camarillo Airport Authority and the Oxnard Airport Authority. Includes correspondence discussing the appointment of members to a mission statement committee for the Oxnard Airport, and correspondence discussing the Five-Year Capital Improvement Plan.